EFEKTIVITAS PENERAPAN BLANDED LEARNING DALAM PEMBELAJARAN SEKOLAH DASAR: - - Moza Musrial; Fadhilah Fransiski; Wiwit Junita Putri; Laila Fitri Hidayatullah; Jefri Albuqori; Denada; Chandra; M. Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information and communication technology has brought changes to education, leading to the emergence of various innovations, one of which is the implementation of blended learning. However, various obstacles remain in its implementation, such as limited internet access, learning devices, and low learning independence among elementary school students. This study aims to as-sess the effectiveness of blended learning in elementary school. This research method utilizes a literature review, reviewing various relevant scientific sources on the application of blended learning. The results of this literature review indicate that blended learning effectively improves student learning outcomes and motivation, critical thinking skills, mathematical literacy, and student learning independence. Furthermore, this learning model provides more flexibility for teachers and students, combining face-to-face and online learning. The novelty of this article lies in the presentation of a study that integrates various research findings on the effectiveness of blended learning in elementary schools, providing a more comprehensive picture of its benefits and application in improving learning quality. Thus, blended learning can be an effective learning model in line with the demands of education in the digital era.